Novel birch pollen specific immunotherapy formulation based on contiguous overlapping peptides. Issue 1 (1st June 2013) - Pellaton, Céline; Perrin, Yannick; Boudousquié, Caroline; Barbier, Nathalie; Wassenberg, Jacqueline; Corradin, Giampietro; Thierry, Anne‐Christine; Audran, Régine; Reymond, Christophe; Spertini, François
Abstract: Background: Synthetic contiguous overlapping peptides (COPs) may represent an alternative to allergen extracts or recombinant allergens for allergen specific immunotherapy. In combination, COPs encompass the entire allergen sequence, providing all potential T cell epitopes, while preventing IgE conformational epitopes of the native allergen. Methods: Individual COPs were derived from the sequence of Bet v 1, the major allergen of birch pollen, and its known crystal structure, and designed to avoid IgE binding. Three sets of COPs were tested in vitro in competition ELISA and basophil degranulation assays. Their in vivo reactivity was determined by intraperitoneal challenge in rBet v 1 sensitized mice as well as by skin prick tests in volunteers with allergic rhinoconjunctivitis to birch pollen. Results: The combination, named AllerT, of three COPs selected for undetectable IgE binding in competition assays and for the absence of basophil activation in vitro was unable to induce anaphylaxis in sensitized mice in contrast to rBet v 1. In addition no positive reactivity to AllerT was observed in skin prick tests in human volunteers allergic to birch pollen. In contrast, a second set of COPs, AllerT4‐T5 displayed some residual IgE binding in competition ELISA and a weak subliminal reactivity to skin prick testing. Conclusions: The hypoallergenicity of contiguous overlapping peptides was confirmed by low, if any, IgE binding activity in vitro, by the absence of basophil activation and the absence of in vivo induction of allergic reactions in mouse and human. Trial registration: ClinicalTrials.gov NCT01719133